Efficiency Assessment of Supply Chain Policy in Fishing Industry Functioning at the Mesolevel - Elena V. Levkina; Natalya Yu. Titova (International Journal of Supply Chain Management, 2019)
Fishery of Primorsky Krai is one of the largest in the system of fishing industry of the Far East and Russia in general that is caused by resource base, an advantageous geopolitical position, favorable climatic conditions in supply chain policy. Increase in efficiency of fishing industry is one of the most important economic problems of Russia and the priority purpose of Primorsky Krai. Recently there was a set of techniques, developments and offers on assessment and increase in efficiency of activity of economic subjects. However, most of them are based on calculation of the indicators reflecting results of activity of the enterprises which function not in a fish complex. Considering structural features of branch systems, the special relevance is acquired by a research of efficiency of economic entities at the mesolevel. In the article author's methodical approach of assessment of efficiency of functioning of fishing industry at the mesolevel is presented. This approach allows not only to estimate in a complex all components of efficiency, but also to consider branch specifics of fishing industry.